EFEKTIVITAS PENDIDIKAN YOGA TERHADAP PENINGKATAN SIKAP SPIRITUAL (KI-1) PESERTA YOGA DI SMK NEGERI 1 SINGARAJA - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This study aims to see the truth of yoga education on improving spiritual attitudes (KI-1) at SMK Negeri 1 Singaraja. The type of experiment used is ex post facto with the prerequisite test of normally distributed data. The data required from observations, interviews, and questionnaires are then processed and analyzed to obtain accurate and reliable results. The results showed that, the implementation of Yoga at SMK Negeri 1 Singaraja was approximately 6 months divided into 1 month of yoga extracurricular activities which can reach 4 meetings, namely in one semester students who take extracurricular Yoga must follow yoga for less than 24 Kali with a teacher or Yogyakarta who has very good abilities. Through trials, the analysis of the spiritual attitudes of yoga participants has the highest value of 0.54 for spiritual attitudes which are classified as effective. This means, the implementation of Yoga is classified as effective in increasing spiritual attitudes.